Dominant negative DISC1 mutant mice display specific social behaviour deficits and aberration in BDNF and cannabinoid receptor expression. (January 2014) - Kaminitz, Ayelet; Barzilay, Ran; Segal, Hadar; Taler, Michal; Offen, Daniel; Gil-Ad, Irit; Mechoulam, Raphael; Weizman, Abraham
Abstract Objectives. Disrupted in schizophrenia 1 (DISC1) is considered the most prominent candidate gene for schizophrenia. In this study, we aimed to characterize behavioural and brain biochemical traits in a mouse expressing a dominant negative DISC1mutant (DN-DISC1). Methods. DN-DISC1 mice underwent behavioural tests to evaluate object recognition, social preference and social novelty seeking. ELISA was conducted on brain tissue to evaluate BDNF levels. Western blot was employed to measure BDNF receptor (TrkB) and cannabinoid receptor CB1. Results. The mutant DISC1 mice displayed deficits in preference to social novelty while both social preference and object recognition were intact. Biochemical analysis of prefrontal cortex and hippocampus revealed a modest reduction in cortical TrkB protein levels of male mice while no differences in BDNF levels were observed. We found sex dependent differences in the expression of cannabinoid-1 receptors. Conclusions. We describe novel behavioural and biochemical abnormalities in the DN-DISC1 mouse model of schizophrenia. The data shows for the first time a possible link between DISC1 mutation and the cannabinoid system.